Symbolic and Ideological Contestation over Humanitarian Emblems: The Red Crescent in Islamizing Indonesia - Hilman Latief (STUDIA ISLAMIKA, 2011)
dikalangan masyarakat mulism Indonesia, kesadaran baru akan peran penting lemaga swadaya masyarakat